Improved survival of patients with primary plasma cell leukemia with VRd or daratumumab‐based quadruplets: A multicenter study by the Greek myeloma study group. Issue 5 (16th March 2023) - Katodritou, Eirini; Kastritis, Efstathios; Dalampira, Dimitra; Delimpasi, Sosana; Spanoudakis, Emmanouil; Labropoulou, Vasiliki; Ntanasis‐Stathopoulos, Ioannis; Gkioka, Annita‐Ioanna; Giannakoulas, Nikos; Kanellias, Nikolaos; Papadopoulou, Theodosia; Sevastoudi, Aggeliki; et al.
Abstract: We evaluated the efficacy and prognostic impact of bortezomib‐lenalidomide triplet (VRd) or daratumumab‐based quadruplets (DBQ) versus previous anti‐myeloma therapies, that is, bortezomib standard combinations (BSC) or conventional chemotherapy (CT), in a large cohort of patients with primary plasma cell leukemia (pPCL), including those fulfilling the revised diagnostic criteria, that is, circulating plasma cells (cPCS): ≥5%; 110 pPCL patients (M/F: 51/59; median age 65 years, range: 44–86) out of 3324 myeloma patients (3%), registered in our database between 2001 and 2021, were studied; 37% had cPCS 5%–19%; 89% received novel combinations including DBQ (21%), VRd (16%) and BSC (52%); 35% underwent autologous stem cell transplantation. 83% achieved objective responses. Treatment with VRd/DBQ strongly correlated with a higher complete response rate (41% vs. 17%; p  = .008). After a median follow‐up of 51 months (95% CI: 45–56), 67 patients died. Early mortality was 3.5%. Progression‐free survival was 16 months (95% CI: 12–19.8), significantly longer in patients treated with VRd/DBQ versus BSC/CT (25 months, 95% CI: 13.5–36.5 vs. 13 months 95% CI: 9–16.8; p  = .03). Median overall survival (OS) was 29 months (95% CI: 19.6–38.3), significantly longer in patients treated with VRd/DBQ versus BSC/CT (not reached vs. 20 months, 95% CI: 14–26; 3‐year OS: 70% vs. 32%, respectively; p  < .001; HzR: 3.88). In the multivariate analysis VRd/DBQ therapy, del17p(+) and PLT <100.000/μL, independently predicted OS ( p  < .05). Our study has demonstrated that in the real‐world setting, treatment with VRd/DBQ induces deep and durable responses and is a strong prognostic factor for OS representing currently the best therapeutic option for pPCL.